THE IMPACT OF RELATIONSHIP STRATEGIES ON SURVIVABILITY OF FIRMS INSIDE SUPPLY NETWORKS - Sofitra, Mohamad; Takahashi, Katsuhiko; Morikawa, Katsumi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
A relationship strategy, which engages firms with each other, mainly intends to achieve a firm’s goals. One goal of such firms is to prolong the firm’s survival in the market. At the supply networks (SN) level, the interactions among firms by means of engaging strategies, i.e. cooperation, defection, competition and co-opetition, are complexly interconnected and coevolved. Due to their complexity and dynamic nature, investigations of the outcomes of the coevolution of interconnected relationship strategies are non-trivial tasks. To overcome these difficulties, this paper proposes cellular automata simulation frameworks and adopts a complex adaptive supply networks perspective to develop a model of the coevolution of interconnected relationship strategies in a supply network. We aimed to determine how and under what conditions the survivability of firms inside supply networks is affected by the coevolution of interconnected relationship strategies among them. We constructed experiments using business environment scenarios of a SN as its factors and observed how different interaction policies of firms could produce networks effects that impact the lifespan of firms. We found that a co-operation coupled with a co-opetition policy in a business environment that favors co-operation can promote the lifespan of nodes at both the individual and SN level.